AN ADVANCED ACFA ARCHITECTURE FOR SECURED LIGHTWEIGHT ENCRYPTION AND DECRYPTION WITH LFSR - JAYASHREE CHAVAN, Dr.AMIT JAIN, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The advanced safety and security mechanisms can be very important in all of the smart applications for 5G communication. Lightweight encryption and decryption enables secure and efficient communication between networked smart objects. The adaptive composite field architecture (ACFA) is 128-bit cipher known to be highly efficient in hardware implementations. Therefore a modified ACFA is required for increasing the safety and security mechanisms in order to overcome the security weakness of the ACFA against attacks. In this proposal, an advanced ACFA architecture for secured Lightweight encryption and decryption with LFSR is presented. This advanced ACFA developed in this uses the Linear Feedback Shift Register (LFSR) designed with semiconductor device technology to overcome the security weakness against attacks. The LFSR is easy to implement in hardware and can be used to create pseudo random number generator that can generate a secure cryptographic key. Then low-cost top-level lightweight encryption/decryption is implemented for 5G communication by integrating the novel s-box approach using the developed advanced ACFA and its performance is analyzed. The proposed architecture can achieve a low area and a high throughput.